The reproductive cycle of Limnoperna fortunei (Dunker, 1857) (Mytilidae) from a neotropical temperate locality - Darrigran, Gustavo Alberto (1999)
Fil: Darrigran, Gustavo Alberto. División Zoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina